Pembaharuan HRIS Dengan Aplikasi FIGMA Di PT. Bank Riau Kepri Syariah - Purnomo, Karin Dwi; Marpaung, Noveri Lysbetti; Hutabarat, Sakti; Ervianto, Edy; halim, Nur; Amri, Rahyul (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2024)
This service activity was carried out in accordance with the needs of PT Bank Riau Kepri Syariah to help manage employee data through updating the existing Human Resource Information system (HRIS). The method used is prototyping with the Figma application to design the user interface and PHP and Laravel for system implementation. System testing was carried out using black box testing and usability testing methods. The results of the activity show that this HRIS system update was successfully implemented to assist in data visualization and reporting. This service activity develops the HRIS system to be user-friendly and easy to understand.